Detection of Mycobacterium leprae infection by PCR. - Wichitwechkarn, J (1995)
PCR amplification of the 531-bp fragment of the Mycobacterium leprae pra gene in fresh biopsy and slit skin smear samples was evaluated for its usefulness in the detection of leprosy bacilli in patients in Thailand. In multibacillary patients, 87.1% (27 of 31) of biopsy specimens and 41.9% (13 of 31) of slit skin smear specimens were positive by PCR, whereas in paucibacillary patients, 36.4% (8 of 22) of biopsy specimens and 18.2% (4 of 22) of slit skin smear specimens yielded detectable PCR amplification. Compared with other diagnostic procedures, PCR showed a clear advantage over both microscopic examination of slit skin smears and serologic detection of anti-phenolic glycolipid 1 antibody, especially in paucibacillary patients when bacterial indexes were 0 and seropositivity was only 6.25%. PCR was also evaluated for its potential to help monitor bacterial clearance in some of these patients during chemotherapeutic treatment. The PCR results on slit skin smear samples at 1, 3, and 6 months of chemotherapy showed that the number of PCR-positive cases of both multibacillary and paucibacillary types decreased sequentially. The results of this study are encouraging. However, investigation of a larger number of clinical specimens with an improvement in PCR methods, especially on slit skin smears, needs to be done before PCR can be established as a diagnostic procedure for leprosy patients and subclinical cases or as a tool for drug assessment.